2021
DOI: 10.1093/g3journal/jkab317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Clostridium beijerinckii strains isolated from pit mud of Chinese strong flavor baijiu ecosystem

Abstract: Clostridium beijerinckii is a well-known anaerobic solventogenic bacterium which inhabits a wide range of different niches. Previously, we isolated five butyrate-producing C. beijerinckii strains from pit mud (PM) of strong-flavor baijiu (SFB) ecosystems. Genome annotation of the five strains showed that they could assimilate various carbon sources as well as ammonium to produce acetate, butyrate, lactate, hydrogen, and esters but did not produce the undesirable flavours isopropanol and acetone, making them us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
3
5
0
Order By: Relevance
“…Furthermore, the fitted curve for the pangenome profile showed that the fitted exponent of the curve was positive, indicating that the pangenome of C. tyrobutyricum is open. This observation is in agreement with the few published reports on this topic on other members of the genus Clostridium cluster I ( Udaondo et al, 2017 ), such as Clostridium baratii ( Silva-Andrade et al, 2022 ), C. perfringens ( Kiu et al, 2017 ; Feng et al, 2020 ), C. beijerinckii ( Sedlar et al, 2021 ; Zou et al, 2021a ), and C. butyricum ( Zou et al, 2021b ). Open pangenomes may indicate the necessity of constant genomic adaptations and diversification to cope with heterogeneous environments ( Medini et al, 2005 ; Rouli et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the fitted curve for the pangenome profile showed that the fitted exponent of the curve was positive, indicating that the pangenome of C. tyrobutyricum is open. This observation is in agreement with the few published reports on this topic on other members of the genus Clostridium cluster I ( Udaondo et al, 2017 ), such as Clostridium baratii ( Silva-Andrade et al, 2022 ), C. perfringens ( Kiu et al, 2017 ; Feng et al, 2020 ), C. beijerinckii ( Sedlar et al, 2021 ; Zou et al, 2021a ), and C. butyricum ( Zou et al, 2021b ). Open pangenomes may indicate the necessity of constant genomic adaptations and diversification to cope with heterogeneous environments ( Medini et al, 2005 ; Rouli et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…Finally, genes with “unknown functions” were enriched in all three pangenome fractions (core, accessory, and strain-specific genes), indicating that there are still many features of C. tyrobutyricum that remain unreported. The over-representation of “function unknown” in the COG categories was similar to what has been observed in other studies of Clostridium species including C. beijerinckii , C. butyricum , and C. ljungdahlii ( Philips et al, 2017 ; Sedlar et al, 2021 ; Zou et al, 2021a ).…”
Section: Resultssupporting
confidence: 85%
“…Of the genomes sequenced for 194 strains classified as C. beijerinckii this study has clearly established these strains belong to 4 different subgroups or subspecies. The DJ genome sequences generated in this study have already been utilized in 3 recently published phylogenetic and taxonomic studies of solvent producing and C. beijerinckii species 7 , 39 , 42 . The C. beijerinckii genomes have provided a resource for comparison with newly isolated strains for 5 butyrate-producing strains from strong-flavor baijiu ecosystems 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In the other investigation undertaken by Zou et al [ 36 ], the genomes of five newly isolated C. beijerinckii strains from pit mud of strong-flavor baijiu ecosystems were sequenced and added to 233 genomes of other C. beijerinckii strains and used for pangenome analysis. The average genome size of the genomes was 6.11 Mb, and the average number of proteins was 5182.…”
Section: Phylogenomics and Phylogeny Of The Solventogenic Clostridiamentioning
confidence: 99%